The Student-Athlete: Procedural Due Process and Property Right - Schubert-Madsen, Cheryl L.; Schubert, George W. (My University, 1989)
This is an overview of due process rights and how they relate to college athletes. It reviews each right (personage, liberty interest, property interest) with relevant court cases up to the time of publication. The authors concluded, "Yet even when each of these elements is present, courts are inclined to defer to the educational and athletic decision-makers and limit the type of notice and hearing that must be afforded."
Keywords: legal issues